CCR9 overexpression promotes T-ALL progression by enhancing cholesterol biosynthesis - Jamal, Muhammad; Lei, Yufei; He, Hengjing; Zeng, Xingruo; Bangash, Hina Iqbal; Xiao, Di; Shao, Liang; Zhou, Fuling; Zhang, Quiping (Frontiers in Pharmacology, 2023)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematological malignancy of the lymphoid progenitor cells, contributing to ~ 20% of the total ALL cases, with a higher prevalence in adults than children. Despite the important role of human T-ALL cell lines in understanding the pathobiology of the disease, a detailed comparison of the tumorigenic potentials of two commonly used T-ALL cell lines, MOLT4 and JURKAT cells, is still lacking. In the present study, comparison of the leukemogenic potentials of the two T-ALL cell lines showed the relatively higher leukemogenic potential of MOLT4 cells, characterized by their enhanced tissue infiltration in NOD-PrkdcscidIL2rgdull (NTG) mice as compared to the JURKAT cells. Gene expression profiling of the two cell lines revealed numerous differentially expressed genes (DEGs), including CC chemokine receptor 9 (CCR9), enriched in vital signaling pathways associated with growth and proliferation. Notably, the upregulation of CCR9 also promoted the tissue infiltration of JURKAT cells in vitro and in NTG mice. Transcriptome analysis revealed that CCR9 overexpression facilitated cholesterol production by upregulating the expression of the core regulatory genes of the cholesterol biosynthesis pathway, including the regulator of the pathway, SREBF2, and the downstream genes: MSMO1, MVD, and HMGCS1, and HMGCR, which was then corroborated at the protein levels.. Notably, simvastatin treatment reduced the migration of the CCR9-overexpressing JURKAT cells, suggesting the importance of cholesterol in T-ALL progression. This study highlights the distinct tumorigenic potentials of two T-ALL cell lines and reveals CCR9-regulated enhanced cholesterol biosynthesis in T-ALL.